Optimization of Distribution Cost of 3kg Gas Cylinder at PT. Gemilang Putra Sejati Using the North West Corner, Least Cost, and Vogel Approximation Method - Nugroho Dimasuharto; Ade Momon Subagyo (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Gas cylinder 3 Kg is one of the elements that is quite important to meet Indonesia's food needs, especially in the use of gas stoves for cooking. This study aims to solve the problem of the cost of shipping 3 Kg gas cylinders at PT. Gemilang Putra Sejati as a gas cylinder distributor company in the Bekasi Regency area. The gas cylinders are stored in warehouses located in 3 sub-districts, namely West Cikarang, Setu and Cibitung, which will be distributed to 5 main agents. Delivery of gas cylinders uses land transportation in the form of 3-wheeled pick-up motors. Shipping costs are calculated based on the total distance from the warehouse to the agent using 3 transportation models, namely the NWC, Least Cost, and VAM methods. The results of the calculation of distribution costs using the NWC method are Rp. 41,760, Least Cost method of Rp. 34,400, and the VAM method of Rp. 33,990. Furthermore, the VAM method is carried out with the final solution using the Stepping Stone method with the result of Rp. 30,090. Then the VAM method can be applied to the companies. Keywords : Optimization, Distribution, VAM method, Least Cost Method, NWC method.